Toxic Cyanobacteria biocontrol by plants - Belhadj, Mokhtar Salah; Abdessalam, Amira (Laghouat : Université Amar Telidji - Département de biologie, 2021)
Toxic cyanobacteria have several negative impacts on aquatic ecosystem, and even harm to humans.Utilization of plants allelochemicals to inhibit microalgal overgrowth is an environmentfriendly approach for controllingHABs.This work aims to sumarize toxic cyanoabcteria biological removal processes using terrestrial and aquatic plants. Several reserch works showed the effiency of plants and their allelochemicals in the removal of both cyanobacterial cells and metabolits released in water bodies aspecially cyanotoxins. The removal of nutrients from water by plants is also proved to have a role in the rehabilitation of aquatic systems and harmful Algae Blooms (HABs) biocontrol.